Methodology of DMAIC with why-why analysis in a hierarchical decision procedure: A case study of quality improvement of polarization maintain and absorption reducing (PANDA) fiber connectors - Wichai Chattinnawat (2018)
This research presents a case study of an efficient and systematic method that combines DMAIC methodology with why-why analysis in a hierarchical decision procedure to improve the quality of PANDA fiber connector. To achieve the zero defect concept, this research procedure identified preventive actions of the production process. The procedure is decomposed into a hierarchy of decisions starting from identifying the Vital Few Causes (VFC) of the product and the process, and removing them from the production process by applying the why-why analysis for identifying their root causes. This systematic procedure led to an easy yet correct identification of the VFCs and provided effective methodology. The improvement leads to a statistically significant reduction in percentage of defect. ©2008 IEEE.